Beteng Cepuri as ethnomathematics of elementary schools - Aziz Murof Suharyanto; Dafid Slamet Setiana; Ana Fitrotun Nisa; Muhammad Irfan (Ethnomathematics Journal, 2022)
Ethnomathematics objects can be found in artifacts in the form of historical buildings. One of the historical buildings in Kotagede, Yogyakarta, Indonesia, is the Beteng Cepuri fortress. The purpose of this research is to conduct an exploration of any mathematical concepts contained in Beteng Cepuri that can be used as a source of learning mathematics as an effort to develop ethnomathematics for learning elementary school mathematics. The researchers invited the fifth-graders of an elementary school in Kotagede, nearby the Cepuri Beteng, to explore and learn mathematical concepts. The results show that there is a relationship between the construction of the fort building and the concept of geometry in several parts of the Cepuri Beteng. The sections are in the form of cuboids and rectangles. Taking the students to visualize the artifacts may assist them to build 3D shape recognition. It can be concluded that ethnomathematics is able to create a very good interest in learning followed by concept acquisition.